Pivotal Role of the C2 Domain of the Smurf1 Ubiquitin Ligase in Substrate Selection - Lu, Kefeng (American Society for Biochemistry and Molecular Biology, 2011)
The C2-WW-HECT-type ubiquitin ligases Smurf1 and Smurf2 play a critical role in embryogenesis and adult bone homeostasis via regulation of bone morphogenetic protein, Wnt, and RhoA signaling pathways. The intramolecular interaction between C2 and HECT domains autoinhibits the ligase activity of Smurf2. However, the role of the Smurf1 C2 domain remains elusive. Here, we show that the C2-HECT autoinhibition mechanism is not observed in Smurf1, and instead its C2 domain functions in substrate selection. The Smurf1 C2 domain exerts a key role in localization to the plasma membrane and endows Smurf1 with differential activity toward RhoA versus Smad5 and Runx2. Crystal structure analysis reveals that the Smurf1 C2 domain possesses a typical anti-parallel β-sandwich fold. Examination of the sulfate-binding site analysis reveals two key lysine residues, Lys-28 and Lys-85, within the C2 domain that are important for Smurf1 localization at the plasma membrane, regulation on cell migration, and robust ligase activity toward RhoA, which further supports a Ca(2+)-independent localization mechanism for Smurf1. These findings demonstrate a previously unidentified role of the Smurf1 C2 domain in substrate selection and cellular localization.